Exenatide promotes regeneration of injured rat sciatic nerve - Kuyucu, Ersin; Gümüş, Bilal; Erbaş, Oytun; Oltulu, Fatih; Bora, Arslan (Wolters Kluwer Medknow Publications, 2017)
Damage to peripheral nerves results in partial or complete dysfunction. After peripheral nerve injuries, a full functional recovery usually cannot be achieved despite the standard surgical repairs. Neurotrophic factors and growth factors stimulate axonal growth and support the viability of nerve cells. The objective of this study is to investigate the neurotrophic effect of exenatide (glucagon like peptide-1 analog) in a rat sciatic nerve neurotmesis model. We injected 10 mg/d exenatide for 12 weeks in the experimental group (n = 12) and 0.1 mL/d saline for 12 weeks in the control group (n = 12). We evaluated nerve regeneration by conducting electrophysiological and motor functional tests. Histological changes were evaluated at weeks 1, 3, 6, and 9. Nerve regeneration was monitored using stereomicroscopy. The electrophysiological and motor functions in rats treated with exenatide were improved at 12 weeks after surgery. Histological examination revealed a significant increase in the number of axons in injured sciatic nerve following exenatide treatment confirmed by stereomicroscopy. In an experimentally induced neurotmesis model in rats, exenatide had a positive effect on nerve regeneration evidenced by electromyography, functional motor tests, histological and stereomicroscopic findings.
WOS: 000400920000028
PubMed ID: 28553346
Keywords: Nerve Regeneration; Sciatic Nerve; Glucagon Like Peptid 1; Electromyography; Stereomicroscopy; Histology; Neural Regeneration